Pure and Confounded Effects of Causal SNPs on Longevity: Insights for Proper Interpretation of Research Findings in GWAS of Populations with Different Genetic Structures - Yashin, Anatoliy I.; Zhbannikov, Ilya; Arbeeva, Liubov; Arbeev, Konstantin G.; Wu, Deqing; Akushevich, Igor; Yashkin, Arseniy; Kovtun, Mikhail; Kulminski, Alexander M.; Stallard, Eric; Kulminskaya, Irina; Ukraintseva, Svetlana (Frontiers in Genetics, 2016)
This paper shows that the effects of causal SNPs on lifespan, estimated through GWAS, may be confounded and the genetic structure of the study population may be responsible for this effect. Simulation experiments show that levels of linkage disequilibrium (LD) and other parameters of the population structure describing connections between two causal SNPs may substantially influence separate estimates of the effect of the causal SNPs on lifespan. This study suggests that differences in LD levels between two causal SNP loci within two study populations may contribute to the failure to replicate previous GWAS findings. The results of this paper also show that successful replication of the results of genetic association studies does not necessarily guarantee proper interpretation of the effect of a causal SNP on lifespan.